Comparison of Coastal Resilience Policies: A Perspective on Effective Global Governance Strategies - Dong Weiwei; Lin Guilan (E3S Web of Conferences)
Coastal areas are key ecosystems that concentrate global biodiversity and are particularly vulnerable to the impacts of climate change. Countries around the world have developed diverse policies to address coastal resilience challenges, responding to threats from sea level rise, extreme weather events, and coastal development. This paper provides a comparative analysis of coastal resilience governance policies across different countries and regions, summarizing successful governance practices. The study reveals that developed countries like the Netherlands and the United States have effectively enhanced disaster resilience and ecological protection by combining hard engineering measures with nature-based solutions. In contrast, countries such as Japan and Indonesia have focused more on community participation and nature-based solutions, demonstrating the advantages of low-cost and sustainable governance. Successful policy tools exhibit several common characteristics, including the integration of engineering measures with nature-based solutions, broad community involvement, multi-level collaborative governance, and adaptive management. Moreover, the study highlights the challenges and prerequisites of cross-regional policy transfer. This paper provides feasible recommendations for policymakers to enhance the adaptability and resilience of coastal areas in response to the long-term risks posed by climate change.